REGULATORY SYSTEMS AT SINUS TACHYCARDIA: HEART RATE VARIABILITY AND SINUS TACHYCARDIA AT PARAINFLUENZA (I+II+III) - Dacenko, E.G. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
A comparative study of the heart rate variability (HRV) indexes in dynamics of an uncomplicated parainfluenza of practically healthy persons with different frequency-adaptive reactions to the disease was performed.It was determined that the patients with different classes of sinus tachycardia (ST), that accompanies the disease under the same clinical manifestation are characterized by different structures of NHR and dynamics of recreational period. The most favorable things for recovery at the top of fever are intermediate capacity of NHR and ST. ST, registered at the top of fever, and activation of a parasympathetic unit of regulation are prognostically favorable factors for influenza.